Customers’ Preference on Selecting an English Course in Pare Kediri in Pandemic Era - Musafik, Mohammad Naim; Kurniawan, Erwin Hari; Sulistyanto, Irwan (Prosiding Seminar, 2022)
Pandemic era have run almost 2 years. And it has affected many things in the educational system around English Course, Pare. Many customers of English course Pare started to consider many things to choose the best English course. Based on those problems, this study attempts to investigate the customer’s perception on their preference of English course. The population of the research as respondents is 48. The sample of the research is 30 experienced alumni of English course who joined the course during pandemic in Pare. To design of this research, descriptive qualitative is chosen. To derive the valid data, Delphi method is applied. This result of this study is expected to provide the evidence of the customers’ perception on their preference of English course. It is showed that some factors affect to the customer’s perception on their preference of English course in Pandemic era.